Conditioning for basketball: Quality and quantity of training - Schelling, X.; Torres-Ronda, L. (Strength and Conditioning Journal, 2013)
The purpose of this paper is to fill the gap on this topic proposing a training methodology for basketball conditioning. The methodology is based on specific progression according to task orientation, approaching levels, and player's individual needs and demands of the approaching levels. This includes training organization, content progression (generic endurance training, high-intensity interval training, repeated-sprint training, with or without changes of direction, small-sided games, and actual basketball), and general recommendations for conditioning training for basketball. The proposed methodology is based on the latest scientific evidence and the authors' practical experience with elite players. For a video abstract of this article, see video supplemental digital content 1, http://links.lww.com/scj/a128